Risk based management of carious lesions in conservative dentistry: an evidence-informed review - Eveline Yulia Darmadi; Yessy Andriani Fauziah; Diana Soesilo; Dwi Setianingtyas; Cindy Hendrawan; Dian Agustin Wahjuningrum (Conservative Dentistry Journal, 2026)
Background: Carious lesions remain one of the most prevalent chronic oral diseases and continue to represent a major indication for operative intervention in conservative dentistry. Variability in diagnostic interpretation and treatment thresholds may compromise long-term outcomes when lesion activity and patient-related risk factors are not systematically considered. Contemporary clinical practice increasingly emphasises risk-based management strategies to enhance biological preservation and improve restorative predictability. Purpose: This evidence-informed review aims to examine current concepts and clinical implications of risk-based diagnostic assessment and treatment planning in the management of carious lesions within conservative dentistry. Reviews: The literature indicates that integration of lesion activity evaluation, individualised caries risk profiling, structured diagnostic systems, and adjunct digital technologies contributes to more consistent and minimally invasive treatment decisions. Risk-oriented approaches support preservation of remineralizable tissues, reduce unnecessary operative procedures, and enhance restoration longevity when combined with preventive reinforcement. Contemporary frameworks encourage a shift from procedure-centred intervention toward patient-centred disease control based on susceptibility and biological criteria. Conclusion: Risk-based management provides a rational and biologically grounded foundation for treating carious lesions in conservative dentistry. Incorporation of individualised risk assessment and lesion activity evaluation into routine clinical protocols strengthens treatment predictability, promotes tissue preservation, and supports sustainable restorative outcomes.